Mathematical Achievements with or without Games in Hinangutdan Public Secondary High School, Samar, Philippines - Ramirez, Cleofe Labanancia; Mercado, Henry Alwayne Rebato (Jurnal Pendidikan Progresif, 2023)
Mathematical Achievements with or without Game in Hinangutdan Public Secondary High School, Samar, Philippines. Objectives: This study determined the effects of games on the mathematics achievement of Grade VII students of Hinangutdan National High School. Method: It utilized quasi-experimental design to establish the effects of teaching with mathematical games (MathDoku, DaMath, Number puzzle, magic squares, and outdoor games races) and without mathematical games on mathematics achievement. There were twenty-eight participants and randomly assigned to the experimental group and the control group. Findings: Results showed a significant higher mean posttest score than mean pretest scores for both groups, suggesting that the two methods are effective. It indicated that teaching with and without mathematical games are equally effective in improving mathematics achievement. Conclusion: It has been determined that using mathematical games in the classroom is effective in raising students' math achievement, particularly in terms of their understanding of basic operations on integers and rational numbers. Notably, teaching mathematical games and without them is beneficial and that both approaches can be combined to teach number operations. Incorporating these games into the classroom, teachers can offer students a variety of presentations of mathematical ideas while also improving their learning experiences.Keywords: mathematical games, pre-test post-test control group experimental design, achievement test.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202323